EDUKASI KESEHATAN JIWA DAN DETEKSI DINI GEJALA DEPRESI PADA LANSIA - Zaman, Badrul; Munawwarah, Khairiyatul; Husna, Nurul; Habibi, Habibi; Faizah, Faizah; Miniharianti, Miniharianti; Bukhari, Bukhari; Nurlaili, Nurlaili (Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
Elderly individuals are vulnerable to depression due to various psychosocial and biological changes; however, the symptoms are often not recognized early. This community service activity aimed to increase the elderly’s understanding of the importance of maintaining mental health and detecting symptoms of depression. The methods used in this community service included the preparation phase, implementation phase, and evaluation phase, involving 20 participants in Jangka Alue Village, Jangka Subdistrict, Bireuen District, on Wednesday, May 21, 2025, from 09:00 to 10:30 AM. Before the educational session, a pre-test questionnaire was given to participants. Following the educational session, a post-test questionnaire was administered to assess the elderly’s understanding. The results of statistical analysis using the Paired Sample T-test showed a significant difference, with a Sig. (2-tailed) value of 0.000 (<0.05). These findings indicate that education and assistance can effectively increase awareness about the importance of maintaining mental health and conducting early detection of depression symptoms among the elderly.